BUSINESS EDUCATORS’ APPRAISAL OF COLLEGES OF EDUCATION BUSINESS EDUCATION CURRICULUM CONTENT FOR ENTREPRENEURIAL SUCCESS IN NIGER DELTA REGION OF NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
In order to execute this study, three research questions were raised and three hypotheses were tested for the study. Descriptive research design was adopted for the study. The entire population of 198 business educators in Bayelsa, Delta and Rivers States of Nigeria were used for the study. Adequacy of Colleges of Education Business Education Curriculum Content for Entrepreneurial Success Questionnaire (ACEBECCESQ) was used for data collection. Cronbach Alpha was used to measure the internal consistency which yielded the reliability co-efficients of 0.83 and 0.76 for cluster B1 and B2 respectively with an overall reliability co-efficient of 0.80.Mean and standard deviation were used to answer research questions while analysis of variance was used to test the hypotheses at 0.05 level of significance. Findings of the study revealed that business educators, irrespective of their years of experience rated the entrepreneurship education and office technology and management curriculum contents as adequate and information communication and technology curriculum content of business education in colleges of education as very inadequate for entrepreneurial success in the Niger Delta region. The study concluded that, absenceof requisite technologies and practical work-based oriented courses that would make the curriculum contents of business education programme meet the modern requirements of the globalized business world is the bane of the un-employability status of business education graduates in Nigeria. The study recommended among others that, the National Commission for Colleges of Education should beef up the curriculum content of business education programmes in colleges of education in Nigeria with trending technological skill courses to enable business education graduates succeed in the 21st century business environment.
Keywords: Education, globalization, business education, curriculum, information communication and technology and entrepreneurship.